Afetos em movimento : esperança e angústia como chaves interpretativas de movimentos sociais - Porto, Douglas Michel Ribeiro (2022)
The affective dimension is not considered in the scope of established theories of social movements. In view of this gap, we seek to sustain in this thesis that social movements are made possible, not despite, but through affections. However, not any affections. Supported by Ernst Bloch, our premise is that affections await special stabilization for the outbreak of movements, hope or anguish. We group social movements around two categories of analysis: utopian-hopeful and utopian-anguishing movements. From the base affection – hope or anguish – we outline the socio-affective conditions that allow the emergence of these movements, the elaboration of their utopias, the conditioning of their identities and their ethical contents. Finally, we analyze the participation of these movements in the processes of fabrication of social reality. From the point of view of Critical Theory, the approach we propose is important and pertinent insofar as it sheds light on a special type of social mediation, that is, social movements, focusing on expectant affects and their centrality to motivate two essential modes of collective action: those that act to preserve an alienating society, and those that act to transform this alienating society and institute a humanizing status quo.